High-frequency ultrasound imaging in wound assessment: current perspectives - Mohafez, Hamidreza; Ahmad, Siti Anom; Hadizadeh, Maryam; Marhaban, Mohammad Hamiruce; Saripan, M. Iqbal (Universiti Putra Malaysia Press, 2017)
Non-invasive imaging modalities for wound assessment have become increasingly popular over the past two decades. The wounds can be developed superficially or from within deep tissues, depending on the nature of the dominant risk factors. Developing a reproducible quantitative method to assess wound-healing status has demonstrated to be a convoluted task. Advances in High-Frequency Ultrasound (HFU) skin scanners have expanded their application as they are cost-effective and reproducible diagnostic tools in dermatology, including for the measurement of skin thickness, the assessment of skin tumours, the estimation of the volume of melanoma and non-melanoma skin cancers, the visualisation of skin structure and the monitoring of the healing of acute and chronic wounds. Previous studies have revealed that HFU images carry dominant parameters and depict the phenomena occurring within deep tissue layers during the wound-healing process. However, the investigations have mostly focussed on the validation of HFU images, and few studies have utilised HFU imaging in quantitative assessment of wound generation and healing. This paper is an introductory review of the important studies proposed by the researchers in the context of wound assessment. The principles of dermasonography are briefly explained, followed by a review of the relevant literature that investigated the wound-healing process and tissue structures within the wound using HFU imaging.